2012
DOI: 10.4172/2155-9600.s2-003
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 Mediates Exercise-Induced Phospholipid Alteration in the Murine Skin Tissues

Abstract: Sciences AbstractWe previously demonstrated that exercise with an iso-caloric diet significantly reduced body weight and skin carcinogenesis in correspondence with lower plasma IGF-1 levels and IGF-1-dependent phospholipid signaling. This study was thus designed to test the hypothesis that IGF-1 reduction plays a causal role in exercise-induced phospholipid changes. SENCAR mice were randomly assigned to one of the following three groups for 12 weeks: ad libitum-fed sedentary control, exercise but pair-fed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
(47 reference statements)
2
11
0
Order By: Relevance
“…36,37 Our lab has shown that IGF-1 restoration within PE mice reversed the reduction of PI phospholipids and PI-associated PI3K. 23 Hence, it appears that IGF-1 is a key growth factor that promotes cancer development in overweight conditions, in part through promoting PI phosphorylation by PI3K and downstream Akt activity which contribute to anti-apoptosis. 38,39 Hence, increased IGF-1-Akt anti-apoptosis, or inhibition of apoptosis, may lead to cancer promotion through turning off protective nuclear apoptosis genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36,37 Our lab has shown that IGF-1 restoration within PE mice reversed the reduction of PI phospholipids and PI-associated PI3K. 23 Hence, it appears that IGF-1 is a key growth factor that promotes cancer development in overweight conditions, in part through promoting PI phosphorylation by PI3K and downstream Akt activity which contribute to anti-apoptosis. 38,39 Hence, increased IGF-1-Akt anti-apoptosis, or inhibition of apoptosis, may lead to cancer promotion through turning off protective nuclear apoptosis genes.…”
Section: Discussionmentioning
confidence: 99%
“…22, 23 In short, each frozen dorsal skin tissue was ground with liquid nitrogen. One gram of tissue was mixed with 2 ml solvent [chloroform/methanol (1:2) + 0.01% butylated hydroxytoluene], 1 ml of chloroform, and 1 ml of water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the analyses mostly focus on the total amount of a particular type of lipid, such as total triglyceride, total cholesterol, and omega-3 fatty acid. With the recent advances in instrumental technology, it is feasible to analyze quantitatively a broad range of lipid species in a single platform [13,15,[30][31][32]. The vast arrays of data generated in lipid profiling studies bring challenges to the statistical analysis of lipidomics data [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…93 In addition, a lipidomics study using electrospray ionization-tandem mass spectrometry demonstrated that 57 phospholipids were significantly changed among a total of 338 species detected, and 25 species were closely related to exercise by a stepwise discriminant analysis. 9394 These combined results indicate that DCR and/or exercise may target IGF-1-dependent signaling directly for a potential cancer prevention.…”
Section: Decreased Igf-1 Signaling In Cancer Preventionmentioning
confidence: 91%